Agreement between personal and maternal body weight perception and weight status in children (Research, Society and Development, 2020)
Background: Obesity rates continue to rise, particularly among children. Studies point to underestimation of body weight as the main factor for non-adherence to weight loss behaviors and that in children, as well as self-perceived underestimation of body size, the same perception reported by parents about the weight of their own children is crucial for the maintenance of overweight and obesity. Thus, it is emphasized that accurate perception of body image by both children and parents is essential to combat the high prevalence of overweight and obesity in the child population. Objective: Evaluate the agreement between the self-perception and maternal perception of children's body weight and their body weight status. Methods: In total, 935 children aged 6 to 10 years, and 922 mothers were evaluated. Body weight status was assessed by means of body weight and height measurements and the perception of body image by means of software for Assessing Child Body Perception. Results: Children classified as "low weight" or "normal weight" demonstrated greater accuracy in their perceptions and a tendency to overestimation in girls whose weight status is "normal", while obese or overweight children tended to overestimate their weight status. Mothers, on the other hand, underestimated their children's weight status, regardless of the sex of their child. Conclusion: Children presented more accurate perceptions than mothers regarding their weight / body size.